ANALISIS KEMAMPUAN SISWA DALAM MEMAHAMI KONSEP SISTEM PERSAMAAN LINIER TIGA VARIABEL (SPLTV) BERDASARKAN TEORI APOS SISWA KELAS X IPS 1 MA TARBIYATUL MUSTAFID BATU RIMPANG - Wahyuningsih, Hasbi; Nissa, Ita Chairun; Yuntawati, Yuntawati (Universitas Pendidikan Mandalika (UNDIKMA), 2019)
This study aims to describe the ability of students to understand the concept of the Three Variable Linear Equation System (SPLTV) based on the APOS theory (Action, Process, Object and Schema) in students of MA Tarbiyatul Mustafid Batu Rimpang. This type of research is a qualitative descriptive study with 3 students subject taken from MA Tarbiyatul Mustafid Batu Rimpang students with high, medium and low ability categories. The results of the study show that highly capable subjects have an understanding of the stages of action, processes, objects and schemes. Subjects who are capable of having understanding at the stage of action, process, object and at the schematic stage students cannot design and complete the mathematical model they form. While low-ability subjects have an understanding of the stages of action, process, object but have not fully arrived at these stages because the subject made a mistake in the calculation process so that the solution given is wrong. The understanding possessed by students with moderate and low ability is the same at the scheme stage.